Confrontation of Immunity and Responsibility Arising from Violation of Jus Cogens Norms in the ICJ Jurisprudence - Mahshid Ajeli lahiji; S. Ali Hosseiniazad; Majid Zahmatkesh (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2023)
Undoubtedly, jus cogens or preemptory norm is always recognized as the highest source of international law. Nevertheless, the judicial review of International Court of Justice caused doubt in the absolute priority of jus cogens when violation of jus cogens and immunity are simultaneously argued in a case. Especially, in the cases concerning the Arrest Warrant (Congo v. Belgium 2002) and the Jurisdictional Immunities (Germany v. Italy 2012), ICJ tried to separate procedural and substantive norms and declared that the norms of immunity and jus cogens are different in nature, thus they couldn’t oppose each other but immunity as a procedural norm could prevent deciding about merits. In this article, by using descriptive – analytic method, the rationale behind the decision of ICJ is analyzed in order to know that if immunity is considered procedural and jus cogens is recognized as substantive norm in international law and how these norms interact. Evaluation of doctrine shows that there is no certainty about the quality of the separation of procedural and substantive norms and their proof in international law. Therefore, the court’s decision in choosing the approach could cause an insecurity in the peremptory place of jus cogens.